Results of a long-term follow-up evaluation of an Australian adult nutrition education program - Pettigrew, Simone; Jongenelis, Michelle; Biagioni, Nicole; Pratt, Steve; Moore, S. (HEC Press, 2018)
Background and Objectives: To assess persistence of improvements in nutrition-related attitudes and behaviours 2-4 years after attending an adult nutrition education program (FOODcents). Methods and Study Design: A link to an online survey was sent to 407 past FOODcents participants. The survey replicated items included in previous FOODcents evaluation surveys. In total, 87 responses were received (response rate 21%). Analyses were conducted on matched responses across 3 time points: pre, post, and follow-up. Results: Improvements since baseline were maintained in confidence to buy healthy foods on a budget and a range of dietary behaviours (e.g., increased consumption of vegetables, legumes, and wholegrain products; greater use of the nutrition information available on food packages; and decreased consumption of soft drinks). There were two primary areas in which improvements were not maintained over time: reported intake of fruit and frequency of consumption of fast food. Conclusions: The results suggest that adult nutrition education can be effective in encouraging individuals to alter their food shopping processes and modify their diets. The tendency for some behavioural outcomes to be worse at follow-up than at baseline indicates that marketplace factors such as food promotion and availability may be influencing these specific dietary behaviours. This rare longitudinal study of the effects of adult nutrition education shows that this form of intervention has the potential to produce lasting improvements in attitudes and behaviours. However, such programs cannot be expected to produce large and lasting effects without support from population-level nutrition policies and programs that address macro-environmental factors that influence dietary behaviours.